1999
DOI: 10.1080/07366299908934644
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Size and Shape Effect in Chemical Isotope Effect of Gadolinium Using Dicyclohexano-18-Crown-6

Abstract: Gadolinium isotopes were fractionated in a liquid-liquid extraction system using dicyclohexano-18-crown-6.The isotope enrichment factors showed breakdowns of the conventional Bigeleisen-Mayer approximation for every condition of the initial phases; the concentrations of gadolinium and hydrochloric acid and the type of organic solvents. The nuclear mass effect and the field shift effect were estimated by use of the isotope pairs 152Gd_I60Gd and 154Gd_16°Gd. Since both isotopes.P'Gd and 154Gd, have the unique ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Ce 4+ reaction may be due to nuclear-volume isotope fractionation, the Ce/ferrihydrite system was unaffected here by the oxidation reaction. A nuclear-volume driven effect was also reported for Nd and Sm (Fujii et al, 1998(Fujii et al, , 2000, but the current study shows that the d 145 Nd vs. d 146 Nd and d 149 Sm vs. d 152 Sm correlations are in accord with a purely mass-dependent isotope effect (Figs. EA2 and EA3), meaning that nuclearvolume driven fractionation was negligible in the experiments.…”
Section: Isotopic Fractionation Between the Liquid And Solid Phasessupporting
confidence: 82%
“…Ce 4+ reaction may be due to nuclear-volume isotope fractionation, the Ce/ferrihydrite system was unaffected here by the oxidation reaction. A nuclear-volume driven effect was also reported for Nd and Sm (Fujii et al, 1998(Fujii et al, , 2000, but the current study shows that the d 145 Nd vs. d 146 Nd and d 149 Sm vs. d 152 Sm correlations are in accord with a purely mass-dependent isotope effect (Figs. EA2 and EA3), meaning that nuclearvolume driven fractionation was negligible in the experiments.…”
Section: Isotopic Fractionation Between the Liquid And Solid Phasessupporting
confidence: 82%
“…These have been confirmed experimentally by chemical exchange methods (solvent extraction or liquid chromatography) with macrocyclic compounds (Fujii et al 1998a(Fujii et al , 1998b(Fujii et al , 1999(Fujii et al , 2001(Fujii et al , 2002a(Fujii et al , 2002b(Fujii et al , 2006bMoynier et al 2008Moynier et al , 2009.…”
Section: Theoretical Background On the Nuclear Field Shift Effectmentioning
confidence: 76%
“…The elements studied include lithium, 1) magnesium, 2) zinc, 3) nickel, 4) samarium, 5) neodymium, 6) gadolinium, 7) strontium, 8) barium, 9,10) chromium, 11) iron, 12) molybdenum, 13) and hafnium. 14) These studies revealed that crown ethers often show large isotope effects, indicating that they could provide isotope separation systems with high performance.…”
Section: Introductionmentioning
confidence: 99%